Lipid Nanoparticles as Carriers for Bioactive Delivery - Dhiman, Neerupma; Awasthi, Rajendra; Sharma, Bhupesh; Kharkwal, Harsha; Kulkarni, Giriraj T. (Frontiers in Chemistry, 2021)
Nanotechnology has made a great impact on the pharmaceutical, biotechnology, food, and cosmetics industries. More than 40% of the approved drugs are lipophilic and have poor solubility. This is the major rate-limiting step that influences the release profile and bioavailability of drugs. Several approaches have been reported to administer lipophilic drugs with improved solubility and bioavailability. Nanotechnology plays a crucial role in the targeted delivery of poorly soluble drugs. Nanotechnology-based drug delivery systems can be classified as solid lipid nanoparticulate drug delivery systems, emulsion-based nanodrug delivery systems, vesicular drug delivery systems, etc. Nanotechnology presents a new frontier in research and development to conquer the limitations coupled with the conventional drug delivery systems through the formation of specific functionalized particles. This review presents a bird's eye view on various aspects of lipid nanoparticles as carriers of bioactive molecules that is, synthesis, characterization, advantage, disadvantage, toxicity, and application in the medical field. Update on recent development in terms of patents and clinical trials of solid lipid nanoparticles (SLNs) and nanostructure lipid carriers (NLCs) have also been discussed in this article.